Dimeric Proanthocyanidins on the Stability of Dentin and Adhesive Biointerfaces. (February 2020) - Leme-Kraus, A.A.; Phansalkar, R.S.; dos Reis, M.C.; Aydin, B.; Sousa, A.B.S.; Alania, Y.; McAlpine, J.; Chen, S.N.; Pauli, G.F.; Bedran-Russo, A.K.
A dentin biomodification strategy with selective proanthocyanidin (PAC)–enriched extracts reinforces dentin and dentin-resin interfaces. Enrichment of the extracts according to the degree of polymerization allows exploration of bioactive principles of PACs and structure-activity relationships. This study investigated the sustained dentin matrix biomodification and dentin-resin bioadhesion of 2 fractions consisting exclusively of B-type PAC dimers with or without a single galloyl motif (specifically, DIMERG and DIMERNG ) and their precursor material, enriched grape seed extract (e-GSE; Vitis vinifera ). The biomodification potential was determined by long-term evaluation of the apparent modulus of elasticity and collagen solubility (hydroxyproline release). Chemical characterization of the dentin matrix was performed by attenuated total reflectance–Fourier-transform infrared spectroscopy. The bioadhesive properties were assessed by a microtensile bond strength test at different time points, and macro-hybrid layers were produced to verify the degree of conversion of the adhesive resin. Fractions consisting of DIMERG, DIMERNG, and their precursor, e-GSE, increased the modulus of elasticity at all time points and reduced collagen degradation. Specimens treated with DIMERNG remained stable throughout 12 mo of storage, whereas a significant drop in the modulus of elasticity was observed for the DIMERG and e-GSE groups at 6 mo. The fractions and precursor did not affect the degree of resin conversion at the hybrid layer. Changes in infrared resonances corresponding to collagen cross-links in the dentin matrix occurred for all treatments. Higher bond strength was observed for dentin treated with e-GSE as compared with DIMERG and DIMERNG ; all biointerfaces remained stable after 12 mo. Nongalloylated PACs mediate stable dentin biomodification, which includes protective activity against collagen degradation and reinforcement of the anchoring dentin matrix. Collectively, PACs with a higher degree of oligomerization offer a robust bioadhesion between the hydrophilic dentin matrix and the hydrophobic adhesive.